Structure and protein recognition of G-quadruplexes - Ngo, Khac Huy (Nanyang Technological University, 2023)
G-rich oligonucleotides can adopt non-canonical secondary structures called G-quadruplexes (G4s) which are biologically relevant and found in applications and nanotechnology. Due to the high structural polymorphism, it is still a challenge to specifically target different G4 structures. In this study, different biophysical, biochemical, and structural techniques (CD, ITC, gel electrophoresis, enzymatic assay NMR spectroscopy, X-ray crystallography) and nucleic acid/protein/peptide engineering were applied to: i) expand our understanding of G4 diversity including base stacking, interlocking, and A•G•G•G•G pentad formation; ii) study the molecular basis for G4 recognition by proteins; iii) engineer G4-binding proteins/peptides for various applications including stable cyclic peptide or engineered enzyme for G4s targeting. The findings from this study provide a better understanding of G4 structures and their recognition by proteins.